A Literary Psychoanalysis of Sophie Treadwell's Machinal: Another Face of a Woman - Abed, Hamid Hammad (Al-Adab Journal, 2015)
This study aims at exploring the woman's chaotic psychology that leads to disastrous end. Treadwell's Machinal reflects the insufferable status of a woman in a time which is greatly affected by unemployment, low production, and poverty that create intensively sensitive psychology. In this play, Sophie Treadwell looks great not merely in her employment of expressionistic technique, but in allowing audience to pinpoint the troubled psyche of her protagonist. Treadwell , as an American playwright, has dealt with the family as a type of her own society. Then, through the psychoanalysis of Machinal, one can discern that it is not always the case where society is responsible for one's depression but a person might victimize himself via his unbalanced psychology